Inflammatory dependent bioresponsive smart transdermal delivery system incorporating susppended nanofibrous mats as a platform for wound healing - Mayet, Naeema (My University, 2016)
The perception of wound healing within the current decade goes beyond the straightforward assertion of the three phases assembling the wound healing cascade. Healing of wounds is a complex process that involves a dynamic series of interactions and reactions and requires a collaboration of the many cell pedigrees, mediators and different tissues. The skin is the largest organ of the body and serves as a protective barrier against foreign objects therefore a loss in its veracity may lead to a decrease quality of life or even death. The primary goal for wound care and treatment is an aesthetically pleasing scar with close to complete functionality at the wound site and rapid wound closure. Attainment of these features requires incorporation of various characteristics such as a moisture retention, absorption and debridgement amongst others. A huge variety of wound dressings are available however not all of these meet the specific requirements of an ideal wound healing device to cover every aspect within the wound healing cascade. Highlighted within this thesis is the design and development of a Bioresponsive transdermal delivery system (BTDS) for wound healing that aims at the incorporation of the significant characteristics for optimal wound management and treatment. Nanobiotechnology is an interdisciplinary field that combines many avenues to revolutionise the development of drug delivery systems specific to wound healing. Delivery systems produced on the nanoscale can encourage the promotion of biologically active new molecular entities that were previously considered underdeveloped by the enhancement of the therapeutic efficacy of wound healing materials. Recent research interest has focused on the development of smart biomaterials. Combining biomaterials that are crucial for wound healing will provide opportunities to synthesize matrices that are inductive to cells and that stimulate and trigger target cell responses crucial to the wound healing process. Stimuli responsive systems provides an attractive, novel and alternate approach to the process of healing by offering an advanced alternative to simple wound dressings as they have the ability to adapt to the surrounding wound environment and regulate the healing process by thermal, chemical, biochemical, electrical and mechanical means on exposure to an external stimulus that triggers the effect. The research focused on the development and characteristic analysis of a complete prototyped device for wound healing incorporating a nanofibrous mat as well as a bioresponsive component to inflammation which could be the first novel prototype developed as an inflammation bioresponsive device for superior wound healing incorporating a nanofibrous mat. The BTDS was synthesized by the attainment of a statistically derived Box- Behnken Design Template, whereby 15 formulations were generated to fabricate a wound healing nanofibrous mats as well as a lyophilized inflammatory dependent matrix. The technique entailed the process of electrospinning for nanofiber formation as well as blending and lyophilization for the inflammatory responsive component. Elucidation of the various polymeric and crosslinker concentrations greatly influenced the properties and characteristics of the system. An endorsement in intensity and conjugation is noted by the FTIR spectra whereby greater shifts in wavelengths from 3260.11cm-1 to 3278.79cm-1 is noted when enhancements in crosslinking bridges is undertaken. Structural morphological analysis revealed the synthesis of smooth, cylindrical, uniformly aligned nanofibres without the presence of nanobeads as well as the formation of a lyophilized matrix having a tough backbone structure at higher concentrations. Upon nanotensile mapping, variation in Young‟s Modulus was observed at 4.25MPa providing flexibility whereas a higher Young‟s Modulus provides rigidity and stiffness to the structure. Determination of the bioresponsive nature was carried out in a stimulated inflammatory environment by utilisation of the Fentons reaction: Fe2+ + H2O2 → Fe3+ + OH∙ + OH- . Results amongst the experimentally derived formulations revealed the reliance of bioactive release on the hyaluronic acid concentration and degradation by hydroxyl radicals present. MDT results obtained depicted a value at 42.39 at a higher hyaluronic concentration and degree of crosslinkage whereas at lower concentrations, MDT values at 33.21 and 35.76 were depicted. In vivo histological examination revealed the healing progression whereby the presence of the nanofibrous mat illucidated a close to complete re-epithelisation and remodelling of the wound site represented by thick, vascular granulation tissue dominated by fibroblasts and extensive collagen deposition. The approach of introducing a topical device for wound management containing both nanotechnology and stimuli responsive techniques provide an innovative and encouraging proposal for wound care to the pharmaceutical industry.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Department of Pharmacy and Pharmacology, Faculty of Health Sciences, University of the Witwatersrand, South Africa Johannesburg 2016